NILAI-NILAI PENDIDIKAN MULTIKULTURAL DALAM NARASI MEDIA SOSIAL NADIRSYAH HOSEN SEBAGAI UPAYA KONTRA WACANA RADIKALISME - Mukhamad Siha Budin; M. Jamhuri; Ahmad Marzuki (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2022)
Education is very important and needs to be considered wisely, in the pro- cess it can be done through social media. One of them is an influential figure, Na- dirsyah Hosen, who has used it as a means to spread the values of multicultural education to respond to various phenomena of radicalism. Therefore, researchers are interested in researching the values of multicultural education in Nadirsyah Hosen's social media narrative as a counter discourse of radicalism This study uses a qualitative approach with the type of content analysis. The content in question is the content of Nadisyah Hosen's Facebook and Insta- gram status updates which were used by researchers as primary data and support- ed by secondary data related to the research in question. Data were collected by observation techniques on social media pages and documentation in the form of photos or images contained on the veranda. Data were collected by using (a) doc- umentation technique. The data analysis technique uses an interactive analysis model by going through three stages, namely data reduction, data presentation, and drawing conclusions. Checking the validity of the data findings is done by triangulation techniques, triangulation of time. The results of this study indicate that efforts to counter Nadirsyah Hosen's discourse of radicalism carried out through social media are as follows: the values of multicultural education in Nadirsyah Hosen's social media narrative as a counter discourse of radicalism, including: the value of tolerance, the value of brotherhood, the value of equality, and the value of justice.